If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + -8 = 6 Reorder the terms: -8 + -1x = 6 Solving -8 + -1x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 6 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 6 + 8 -1x = 6 + 8 Combine like terms: 6 + 8 = 14 -1x = 14 Divide each side by '-1'. x = -14 Simplifying x = -14
| -4x+5=3x+16 | | 5(1/5+c)=2/2/3 | | 2/3*5/6*14 | | 3(x+2)-4x=-2(x-3) | | 11.5=y | | 2y+3(y-2)=8y-5(y+10) | | -27+4-5= | | 56+38x= | | (x)(x+1)=156 | | 43*17= | | 5+36-13=13 | | -2-6x=52 | | 13=5+36-13 | | 2*4+6= | | 16t^2-96t-96=0 | | 204=4-10n | | -29=11p/59 | | 5(4X+3)=175 | | .5x(2x+2)=110 | | 1/2/3+3n=4/5n+15 | | 3x+4=12+7x | | 2y-10=-18 | | 52=4a | | (x+1)(x+2)=30 | | 4x=6x+20 | | 10-2.7=y+9 | | x-7.7=-5.5 | | 6+(4+7)=(6+4)+7 | | -3x+3x=0 | | -8=p/12 | | 112/14 | | 16x=-240 |